Valorization of agroindustry waste for the elaboration of fishburgers (Research, Society and Development, 2021)
Waste production derived from agroindustry (bark, bagasse and seeds) has been increasing in Brazil. The cultivation of cashew to produce chestnuts and products obtained from cashew peduncle has generated a large amount of residue. Therefore, the objective of this study was to elaborate Nile tilapia fishburger with addition of cashew residue flour (CRF) and evaluate its microbiological and physicochemical characteristics. Three formulations F0, F1 and F2 (0%, 5% and 10% CRF, respectively) were elaborated as a substitute for mechanically separated meat (MSM) from Nile tilapia. The results of the microbiological analyzes of CRF and fishburgers were satisfactory, according to standards established by the Brazilian legislation. Fishburger formulations showed low lipid and high protein content. The analysis of centesimal composition showed that there was no significant difference (p≥0.05) between the formulations (except water content and carbohydrate). The results show the elaboration of new products based on the residues of agroindustry provides greater access of fish products to different social classes and waste valorization. CRF has been applied to fishburger formulations satisfactorily, helping to reduce the environmental impacts associated with the disposal of this agroindustrial waste.